Kajian Sosiologi Sastra Menggali Identitas Budaya Pada Legenda Gunung Kelud : Kajian Sosiologi Sastra Menggali Identitas Budaya Pada Legenda Gunung Kelud - Insani Wahyu Mubarok; Mayaza Dini (Universitas Muhammadiyah Surabaya, 2026)
This study aims to reveal the elements contained in the Legend of Mount Kelud, which reflect the cultural identity of the surrounding community. Through a sociological analysis of literature, this study examines the relationship between folklore and the daily lives of the community, as well as its role in preserving culture and morals. The method used in this study is a historical approach using normative and interpretative analysis. Data were collected through observation, recording, and analysis of documents sourced from books and articles related to the legend of Mount Kelud. The results of the study indicate that the legend of Mount Kelud has a strong relevance in the lives of the community, especially in traditional practices such as ruwatan (traditional rituals) and larung sesaji (offerings). This legend serves as a guardian of cultural identity, strengthens social solidarity, and teaches spiritual and moral values ​​related to the balance of nature. In addition, this legend also plays a role in introducing and preserving local culture, and is an important part of the oral tradition passed down from generation to generation.. Keywords: : Sociology of literature, Cultural Identity, Mount Kelud